Sustainable development strategy in response to the aging population challenge in Vietnam - Tuyết, Trần Thị Minh; Cường, Nguyễn Anh (International Journal of Innovative Research and Scientific Studies, 2025)
Vietnam is experiencing one of the fastest population aging transitions globally, shifting from a demographic dividend to an aged society within a short period. This phenomenon poses significant socio-economic challenges, including pressures on the healthcare system, social welfare programs, and the labor force. This study employs a mixed-methods approach, combining quantitative and qualitative analysis, drawing on data from the General Statistics Office of Vietnam, Vietnamese government policy documents, and global reports by the United Nations Population Fund (UNFPA). The findings highlight a rapid demographic shift characterized by declining fertility rates and increased life expectancy, which profoundly impacts labor productivity, healthcare costs, and the social security system. The study proposes solutions such as improving healthcare infrastructure, reforming retirement policies, and enhancing family support systems to mitigate adverse effects. These policy recommendations aim to help Vietnam adapt to population aging and provide valuable lessons for other developing countries facing similar demographic transitions.